Advertising, gender, and consumer culture in Bangladesh - Iqbal Ahmed Chowdhury (Humanities & Social Sciences Communications)
Abstract Advertising is one of the media that contributes to cultural diffusion. This paper analyzes whether television advertising can diffuse new cultural practices and reinforce existing ones for female consumers in Bangladesh. Grounded in the “cultivation theory” of George Gerbner and the “responsive chord theory” of Tony Schwartz, as well as the theories of consumer culture and femvertising, it analyzes prime-time television advertising of the three most-watched Bangladeshi television channels along with data collected from 60 in-depth interviews. The results reveal that Bangladeshi television advertisements often introduce new cultures for women consumers whereby they can challenge existing stereotypical gendered practices including riding bicycles and going out of home alone. In addition, advertisements also reinforce existing gendered cultural practices that inform patriarchal values (particularly in rural areas) in that women’s primary goal is to satisfy family members and stay at home. The study also finds that women living in urban areas tend to challenge the existing patriarchal obligations, while rural women follow these obligations. The paper enhances our understanding of the relationship between advertisements and gendered cultural practices.